Exploring effective strategies for health education in schools: a systematic review - Mokhtar, Rahmat Sholihin; Nasri, Nurfaradilla Mohamad; Wan Pa, Wan Ahmad Munsif (Intelektual Pustaka Media Utama, 2025)
Considering the pressing need for effective health education in primary schools, this systematic review rigorously evaluates various strategies designed to enhance students’ health knowledge, attitudes, and behaviours. The primary objective of this study is to assess the efficacy, challenges, and outcomes of health education programmes that utilise interactive and participatory methods, such as project-based learning and peer education. The study methodology adheres to the preferred reporting items for systematic reviews and meta-analyses or PRISMA framework. Utilising advanced search techniques across Scopus and Web of Science (WoS) databases, a total of (n=35) relevant studies between 2020 to 2024 were identified and subjected to thorough analysis. This article synthesizes findings from the final articles into three main themes: Integrative approach in health education, digital and distance learning strategies (DDLS), and ethical and cultural challenges in health education. This review underscores the critical importance of integrating health education within the broader school curriculum, actively involving parents and the community, and implementing culturally tailored approaches. The review shows positive outcomes but also highlights the need for better teacher training and resource allocation, requiring collaboration from educators and policymakers. It emphasizes the potential of these strategies to foster lifelong healthy behaviors and calls for more research to address challenges and assess long-term effects.